2015
DOI: 10.1111/pcn.12270
|View full text |Cite
|
Sign up to set email alerts
|

Tardive dyskinesia (syndrome): Current concept and modern approaches to its management

Abstract: Tardive dyskinesia is a serious, disabling and potentially permanent, neurological hyperkinetic movement disorder that occurs after months or years of taking psychotropic drugs. The pathophysiology of tardive dyskinesia is complex, multifactorial and still not fully understood. A number of drugs were tried for the management of this motor disturbance, yet until now no effective and standard treatment has been found. It is very disappointing to realize that the introduction of antipsychotics from the second gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 130 publications
1
71
0
6
Order By: Relevance
“…Based on currently available information, no confident statement can be made about the effectiveness of anticholinergics Tardive dyskinesia: identification and management 7 to treat TD and in fact benzhexol or benztropine or biperiden or orphenadrine or procyclidine or scopolamine or trihexyphenidyl, and other anticholinergics tend to aggravate abnormal movements and in some cases elicits abnormal movement not previously observed [41,43]. This evidence supports the hypothesis that anticholinergic therapy in patients prone to develop TD may increase the incidence of this disorder.…”
Section: Anticholinergic Drugssupporting
confidence: 60%
See 3 more Smart Citations
“…Based on currently available information, no confident statement can be made about the effectiveness of anticholinergics Tardive dyskinesia: identification and management 7 to treat TD and in fact benzhexol or benztropine or biperiden or orphenadrine or procyclidine or scopolamine or trihexyphenidyl, and other anticholinergics tend to aggravate abnormal movements and in some cases elicits abnormal movement not previously observed [41,43]. This evidence supports the hypothesis that anticholinergic therapy in patients prone to develop TD may increase the incidence of this disorder.…”
Section: Anticholinergic Drugssupporting
confidence: 60%
“…Clonazepam [41,[43][44][45][46] Studies of clonazepam the GABA-A agonist benzodiazepine (BZ) showed some effect in reducing TD [41,43]. Although no specific adverse effects would limit the usefulness of clonazepam in the elderly; the risk of drug interactions, psychomotor slowing, increased rate of falls with hip and femur …”
Section: Treatment and Managementmentioning
confidence: 97%
See 2 more Smart Citations
“…It is usually nonreversible and has a prevalence rate of about 24% in a review conducted in 1988 [14]. However with the advent of newer atypical antipsychotics, a 2.5 fold reduction has been noted and the incidence rate at present is around 2% [15].…”
Section: Discussionmentioning
confidence: 99%